VALUATION AND EVALUATION IN COMPLEX REAL SYSTEMS: A SYNERGISTIC MAPPING AND POLICY TEMPLATE - Ravetz, Joe (BDC. Bollettino Del Centro Calza Bini, 2014)
This paper explores methods for valuation and evaluation, which are suitable for complex inter-connected “real” systems. Urban cultural heritage sites, or urban ecosystems, often contain multiple sources of value (economic, social cultural, ecological): such value is often generated by multiple collaborations, social learning and collective intelligence, and there are multiple policy objectives and system inter-connections to be evaluated. In contrast to the normal reductive assumptions of mainstream valuation/evaluation, such highly inter-connected situations call for new methods. This paper demonstrates the “synergistic” approach to valuation and evaluation, with a practical “evaluation template”, and some examples from “Greater Manchester”, UK. Keywords: synergistic approach, evaluation template, Greater Manchester